The status of southern white-cheeked gibbon (Nomascus siki) in Truong Son key biodiversity area - Duy, Nguyen Dinh; Can, Dang Ngoc; Trai, Le Trong; Ninh, Le Van; Hieu, Tran Dang; Nghia, Ha Van; Mai, Trinh Thi; Tu, Ly Ngoc (Academia Journal of Biology, 2020)
The Southern white-cheeked crested gibbon, Nomascus siki, is an endemic primate to Vietnam and Laos, and has been identified as a nationally and globally endangered species (EN). However, little information is known on the status of the species in Vietnam generally and in the Truong Son key biodiversity area (Truong Son KBA) particularly. In order to explore the current status of the species in the Truong Son KBA, we conducted field surveys in 2018 and 2019. Analysis of the survey data shows 149 groups of gibbon in the 4 study areas. Combined with results of similar-techniqued survey in 2016 on the same species in Khe Nuoc Trong forest, we identified at least 252 gibbon groups and estimated 425 gibbon groups in the entire Truong Son KBA. These gibbon groups are mainly distributed in medium-rich evergreen closed forests in mountainous areas of the west Truong Son KBA, adjacent to the Vietnam-Laos border.